Hey Buddy : in pursuit of Buddy Holly, my new buddy John, and my lost decade of music - Moore, Gary W. (Gary Warren), 1954- (Savas Beatie, 2011)
The "thoroughly fun ... [and] crazy good" memoir about one man's life and how it was changed by the legacy of a rockabilly legend (Chicago Sun-Times). Buddy Holly, icon: black horn-rimmed glasses, blue jeans, a white T-shirt, white socks, loafers, and "Peggy Sue." Not so much to Gary W. Moore. Admitting he "grew up in a Rock & Roll vacuum," Gary favored jazz. He couldn't name a single Buddy Holly song. Buddy Rich' Yes. But that changed in a single evening when Gary was dragged along to a Winter Dance Party in Cedar Falls, Iowa-a tribute to Buddy's final, tragic 1959 tour. It was headlined by musician extraordinaire John Mueller, whose uncanny recreation of the legend was hailed by Buddy's own brother Travis as "the best I've ever seen." It took just one song to seize Gary's heart and soul. From then on, for Gary, it was everything Buddy. In this inspiring "rock-and-rollercoaster of a read", Moore shares his personal journey to learn more about Buddy's life, music, his influence, his impact, and the times in which he lived (Bill Guertin, author of Reality Sells). He'd meet Buddy's friends and family, celebrities, Buddy Holly fans, and make a new friend himself in John Mueller. The result is "as American as apple pie and as compelling as Don McLean's legendary hit about The Day the Music Died" (James Riordan, New York Times-bestselling author)